New Initiative on postgraduate developments in social work in Europe - Darja Zavirsek (Social Work and Society)
In September 2004 five European Schools for social work started to develop an international doctoral studies program in social work. The initiative came from the Faculty of Social Work Ljubljana and the meeting was held in Ljubljana, Slovenia. The partners designed a mission statement which is now published for the first time.